Discourses of Professionalism in Front-Line Service Work: Insights from a Case Study in an Italian Bank. (October 2019) - Carollo, Luca; Solari, Luca
The article draws on the literature on the triangular employment relationship in the service industry, as well as on the debate on contemporary forms of professionalism, to explore the varied uses of the discourse of professionalism in a banking company. Methodologically, it is a single-case study based on 61 semi-structured interviews, company documents and observational data. The research results show how, in the company studied, the notion of professionalism was used both by individual employees and, at the collective level, by union organizations to advance front-line employees' and customers' interests vis-a-vis the management. Moreover, rather than a single discourse, several discourses of professionalism coexisted within the company, and they were subject to constant debate and contestation. The article thus advances extant research on both contemporary forms of service work and professionalism, while providing a bridge between these two streams of literature which, to date, have barely talked to each other.